Breakage mechanism of brown rice grain during rubber roll hulling. (January 2023) - Chen, Peiyu; Jia, Fuguo; Zhang, Jincheng; Han, Yanlong; Li, Anqi; Wang, Yinglong; Fei, Jiaming; Shen, Shaohang; Feng, Wenyu; Hao, Xianzhi
Abstract : Rice grains breakage during hulling in a rubber roll huller influences the desired final rice quality and thus its economic value. Clarifying the grains breakage mechanism in the hulling process is the key to reducing the breakage ratio and improving quality. The breakage mechanism was clarified by quasi-static compression, three-point bending, compression-shear and hulling tests. The results show that rigid compression and three-point bending breakage cannot be used to characterise grains breakage mechanism in the hulling process, and flexible compression cannot break grains. The breakage mechanism involved is flexible compression; the application of shear load rotates grains resulting in the action of bending and shear and this finally produces bending tension and shear failure. Shear force and pressure increase with the increase of shear direction, resulting in increasing breakage ratio. Highlights: Rice grain breakage is not caused by excessive pressure in the hulling process. Shearing force is closely related to the grain breakage in the hulling process. Grain breakage is caused by bending tension and shear breakage. Limiting the rotation of grains can reduce breakage ratio in the hulling process.